2005
DOI: 10.1051/vetres:2004060
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Duddingtonia flagrans chlamydospores to goats to control gastro-intestinal nematodes: dose trials

Abstract: -The ability of the nematophagous fungus Duddingtonia flagrans to reduce the number of infective nematode larvae in coproculture was investigated in goats using different doses of chlamydospores (0, 1.25 × 10 5 , 2.5 × 10 5 , 5 × 10 5 chlamydospores/kg BW/day) given by oral administration or by voluntary consumption in feed during natural or experimental infections with nematodes. The kinetics of excretion of D. flagrans chlamydospores in the faeces was also determined using a dose of 5 × 10 5 chlamydospores/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
2
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 27 publications
3
22
2
2
Order By: Relevance
“…Previous results have demonstrated that the nematode destroying effects of fungi on Trichostrongylidae parasites in faecal cultures [1,11,19] may be reflected in reduced pasture contamination under field grazing conditions [27]. However, the results herein showed that GI nematode species were affected differently by treatment.…”
Section: Effect Of Nematophagous Fungi and Energy Supplement On Parascontrasting
confidence: 53%
“…Previous results have demonstrated that the nematode destroying effects of fungi on Trichostrongylidae parasites in faecal cultures [1,11,19] may be reflected in reduced pasture contamination under field grazing conditions [27]. However, the results herein showed that GI nematode species were affected differently by treatment.…”
Section: Effect Of Nematophagous Fungi and Energy Supplement On Parascontrasting
confidence: 53%
“…Despite poor cytological descriptions or documentation of their mode of generation, chlamydospores have been observed in three major clades of the fungal kingdom. For example, the basidiomycete black ink mushroom Coprinus cinereus (28) and Cryptococcus laurentii (30), the ascomycete nematode-trapping fungus Duddingtonia flagrans (20,41), and zygomycete mucorales, such as Rhizopus schipperae (4,55), have all been shown to produce chlamydospores. Even the fungus-like oomycete plant pathogens Phytophthora cinnamomi and Phytophthora parasitica produce chlamydospores.…”
mentioning
confidence: 99%
“…For example, desiccation-resistant chlamydospores of P. cinnamomi are produced within plant roots during drought and are transported in root fragments or soil, germinating to cause infections when warm, moist conditions are encountered. When chlamydospores of the nematode-trapping fungus D. flagrans are fed to domesticated animals, they can survive passage through the alimentary tract and reduce the number of parasitic nematode larvae that develop from eggs in the feces, thus preventing clinical disease (20,41). In addition, the chlamydospore developmental phase of Aspergillus parasiticus has been associated with increased aflatoxin production, while chlamydospores of Fusarium species are the principal means of long-term survival during unfavorable periods in the soil and play an important role as the primary inocula infecting plants (1,14).…”
mentioning
confidence: 99%
“…Among the endoparasitic fungi, those reported to infect H. contortus are Drechumeria coniospora and Harposporium anguillulae while Arthrobotrys oligospora and A. robusta are predacious fungi of different species of Haemonchus (Larsen, 2000). A significant breakthrough in this area was reported by a number of studies using the species, Duddingtonia flagrans (Waller et al, 2001;Fontenot et al, 2003;Chandrawathani et al, 2004;Paraud et al, 2005). This predacious fungus produces three dimensional sticky networks, which tightly traps free-living nematode larvae in the faeces ultimately resulting in their death.…”
Section: Biological Control: Use Of Fungal Sporesmentioning
confidence: 99%
“…Despite its appreciable degree of efficacy, this method of parasite control is still not widely applicable. This may be attributed largely to the requirement for continuous oral or in-feed dosing with fungal spores to achieve the desired level of efficacy (Terrill et al, 2004;Paraud et al, 2005). Also the chlamydospores have a relatively short shelf life (less than one week) in a moist environment, which enables the fungal spores to start to germinate and become vulnerable to degradation during their passage through the animal host (Larsen, 2006).…”
Section: Biological Control: Use Of Fungal Sporesmentioning
confidence: 99%